Bayes Without Bernoulli: Simple Conditions for Probabilistically Sophisticated Choice - Mark J. Machina; David Schmeidler (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1994)
In 1963, Anscombe and Aumann demonstrated that the introduction of an objective randomizing device into the Savage setting of subjective uncertainty considerably simplified the derivation of subjective probability from a decision maker's preferences over uncertain bets. The purpose of this paper is to present a more general derivation of classical subjective probability in such a framework, which neither assumes nor implies that the individual's risk preferences necessarily conform to the expected utility principle. We argue that the essence of "Bayesian rationality" is the assignment, correct manipulation, and proper updating of subjective event probablities when evaluating and comparing uncertain prospects, regardless of whether attitudes toward risk satisfy the expected utility property.
Keywords: 330